Pola Komunikasi Interpersonal Orang Tua dan Anak pada Keluarga Broken Home - Sihabuddin, Nafsah Khairiyyah; Nahuway, Johana (Jurnal Ilmu Komunikasi Pattimura, 2022)
Abstract : Broken Homes often occur in social life, especially in divorce cases, with various causes that make husband and wife decide to divorce. As a result of the divorce, one parent must leave the house and the child must choose one of them. The impact that arises as a result of this divorce is the communication process that exists between parents and children who do not live together. Therefore, family communication patterns are very important in family relationships even though they are separated. In general, the purpose of this research is to determine the communication patterns of parents and children in broken home families. The theory used is the pattern of family communication using qualitative research methods. Data collection techniques used are observation and in-depth interviews. The results obtained are: communication patterns of parents and children using family communication patterns consisting of equation communication patterns, separate balanced communication patterns, separate unbalanced communication patterns, and monopoly communication patterns. It can be concluded that the communication pattern of parents and children after the divorce has an impact on the relationship and changes in the nature of parents and children. So it can be said that a broken home has an impact on the relationship between parents and children and their personality. Keywords : Broken Home, Divorce, Communication Pattern